Designing Passive Harmonic Filter on Dynamic Positioning Vessel's Electrical System Affected using Electrical Thruster - Sardono Sarwito; Indra Ranu Kusuma; Yose Gregory Tarigan (Institut Teknologi Sepuluh Nopember, 2019)
Ship with a dynamic positioning system has the ability to maintain her position dynamically. To be able to maintain the position, generally, ship with a dynamic positioning system have several thrusters located at bow or stern of the ship. Based on the propulsion system, there are 2 types of thruster which are mechanical thruster and electrical thruster. In electrical type, the thruster is driven by an electric motor supplied from the generator. In addition, on dynamic positioning vessel equipped with the electrical thruster, there are also VFD or Variable Frequency Drive to control the speed of motor thruster. The use of VFD components in the system may cause harmonic interference. Harmonic itself can be regarded as distortion in the sinusoidal waves due to the interference of other waves that have integer frequency multiples of their fundamental frequency due to the operation of non-linear thruster motor. Some of the most affected components of this distortion are the communications equipment and the components used for measurement. This research conducted an analysis of harmonic disturbance arising from the operation of 2 units bow thruster on DP Ship by simulating 6 scenarios of generator configuration using simulation software. The results from this research were total harmonic distortion value or VTHD of the system that complies with standards and rules, also the specification of a passive harmonic filter to reduce the VTHD value at the specific harmonic order.